1999
DOI: 10.1159/000014177
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Arginine Levels and the Response to Inhaled Nitric Oxide in Neonates

Abstract: Inhaled nitric oxide (iNO) can be an effective vasodilator in pulmonary hypertension of the newborn (PHN). The aim of this study was to determine whether differences in arginine levels, from which endogenous NO is produced, explain the variability in response to NO and whether the arginine levels were lower in term and preterm infants with PHN than in infants without PHN (controls). We prospectively studied 30 infants (17 born preterm) with clinically diagnosed PHN and treated with iNO and 22 controls (14 born… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Previous studies showed that differences in plasma L-arginine concentrations did not explain the variation in response to inhaled NO therapy. 35 In this study, we obtained arterial blood samples immediately after birth so that the concentrations of the measured markers were not modified by ongoing management. Previously, when blood samples were obtained 18 to 40 hours after birth, ET-1 concentrations correlated with duration of mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that differences in plasma L-arginine concentrations did not explain the variation in response to inhaled NO therapy. 35 In this study, we obtained arterial blood samples immediately after birth so that the concentrations of the measured markers were not modified by ongoing management. Previously, when blood samples were obtained 18 to 40 hours after birth, ET-1 concentrations correlated with duration of mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…Small case reports suggest that sildenafil increases cGMP and facilitates weaning of infants with PPHN from iNO (23) and that use of inhaled PGI 2 can induce rapid improvement in oxygenation in neonates with PPHN refractory to iNO (20). Arginine levels are lower in term and preterm neonates with PH compared with controls (24). Uncontrolled trials suggest improved oxygenation with L-arginine infusion in infants with PPHN (25).…”
mentioning
confidence: 99%